Local Wisdom-Based Da'wah Rhetoric: Analysis of Guru’s Communication Styles in South Kalimantan - Rahmah, Mariyatul Norhidayati; Nuwairah, Nahed; Amaly, Najla; Rani, Samsul (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
Although previous studies have examined rhetorical strategies in da’wah (Islamic preaching), limited attention has been given to how these strategies adapt to specific local cultures. This study addresses that gap by exploring how Islamic preachers (Guru) in South Kalimantan incorporate Banjar cultural values into their rhetorical practices to enhance message relevance and audience engagement. The study aims to identify the dominant rhetorical styles used, explain how they draw from local wisdom, and assess their communicative impact. A qualitative-descriptive method within the ethnography of communication framework was employed. Data were collected through direct observation, in-depth interviews with preachers and congregants, and sermon documentation. Thematic coding and interpretive analysis were used to link rhetorical patterns with Banjar cultural elements. Findings reveal three dominant rhetorical styles: (1) persuasive-narrative, utilizing local folklore such as Hikayat Datu Kalampayan; (2) religious humor, incorporating Banjar comedic expressions to build rapport; and (3) symbolic-cultural references, invoking values like baimbai (cooperation) and adat basambangan (etiquette in interaction). These strategies reduce social distance, strengthen emotional connection, and improve audience receptivity. The study contributes theoretically by highlighting the cultural embedding of rhetorical forms in localized da’wah. Practically, it offers a model for preachers to contextualize messages effectively. It also suggests integrating cultural adaptation training into preacher development programs.